A Romerian Contribution to the Empirics of Economic Growth - Bahar Bayraktar Sağlam; I. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2012)
Mankiw Romer and Weil (1992) made the Solovian set up widely-used to test the determinants of economic growth and the speed of convergence. Subsequently, in almost all convergence studies, an exogenously growing technology is assumed and this component is treated as part of the constant term. In this study, we expand the Mankiw Romer and Weil (1992) set-up through a Solovianized Romer (1990) framework, which allows us to decompose the exogenously growing technological progress. Within this framework, the growth rate of technology depends on the characteristics of the R&D sector, including the share of labor devoted to R&D activities. We estimate the convergence equation derived from Solovianized Romer model for 31 OECD countries for the period 1980-2008 by applying the system GMM approach. The empirical findings of the model supports the conditional convergence hypothesis, but predicts a much lower convergence rate (0.01) than that predicted by the existing empirical growth literature (0.02). The model supports the positive and significant role of R&D on economic growth. Another contribution of the model is the elegant introduction of human capital to the convergence equation.
Keywords: O30; O47; O50; C23; 330; Convergence; Economic Growth; Exogenous Technological Change; Wirtschaftliche Konvergenz; Technischer Fortschritt; Wachstumstheorie; Wirtschaftswachstum; OECD-Staaten